Efficacy and Safety of Clopidogrel in the Prevention of Primary Failure of Arteriovenous Fistula in Patients with End-Stage Renal Disease: A Systematic Review - Wahyudi Wahyudi; Dono Antono; Pringgodigdo Nugroho; Ikhwan Rinaldi; Ika Prasetya Wijaya; Hamzah Shatri; Em Yunir; Lusiani Rusdi (Acta Medica Indonesiana)
Background: Arteriovenous fistula (FAV) is the most widely used vascular access for end-stage renal disease (ESRD) patients undergoing routine hemodialysis in Indonesia. However, FAV can become dysfunctional before it is used for the initiation of hemodialysis, a condition known as primary failure. Clopidogrel is an anti-platelet aggregation that has been reported to reduce the incidence of primary failure in FAV compared to other anti-platelet aggregation agents. Through this systematic review, we aimed to assess the role of clopidogrel to the incidence of primary FAV failure and the risk of bleeding in ESRD patients. Methods: A literature search was carried out to obtain randomized Control Trial studies conducted since 1987 from Medline / Pubmed, EbscoHost, Embase, Proquest, Scopus, and Cochrane Central without language restrictions. Risk of bias assessment was performed with the Cochrane Risk of Bias 2 application. Results: All of the three studies involved indicated the benefit of clopidogrel for the prevention of AVF primary failure. However, all of the studies have substantial differences. Abacilar’s study included only participants with diabetes mellitus. This study also administered a combination of clopidogrel 75 mg and prostacyclin 200 mg/day, while Dember’s study gave an initial dose of clopidogrel 300 mg followed by daily dose 75 mg and Ghorbani’s study only gave clopidogrel 75 mg/day. Ghorbani and Abacilar started the intervention 7-10 days before AVF creation, while Dember started 1 day after VAF creation. Dember gave treatment for 6 weeks with an assessment of primary failure at the end of week 6, Ghorbani’s treatment lasted for 6 weeks with an assessment at week 8, while Abacilar gave treatment for one year with an assessment at weeks 4 after AVF creation. In addition, the prevalence of bleeding did not differ between the treatment and control groups. Conclusion: Clopidogrel can reduce the incidence of primary FAV failure without significant increase of bleeding events.